2011
DOI: 10.1098/rstb.2011.0155
|View full text |Cite
|
Sign up to set email alerts
|

Flow sensing by pinniped whiskers

Abstract: Beside their haptic function, vibrissae of harbour seals (Phocidae) and California sea lions (Otariidae) both represent highly sensitive hydrodynamic receptor systems, although their vibrissal hair shafts differ considerably in structure. To quantify the sensory performance of both hair types, isolated single whiskers were used to measure vortex shedding frequencies produced in the wake of a cylinder immersed in a rotational flow tank. These measurements revealed that both whisker types were able to detect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 47 publications
(53 reference statements)
4
77
0
Order By: Relevance
“…For both types of whiskers the researchers cal- culated a signal-to-noise ratio (SNR), or ratio of the power between 'wanted' signals and background noise. Results showed that while both whisker types responded accurately to vortices in the water tank, as supported by the aforementioned studies of these species, harbor seal whiskers significantly reduced background noise compared to California sea lion whiskers (Miersch et al, 2011). Walruses are the other members of the pinnipeds, but the role of their whiskers is largely unexplored.…”
Section: Somatosensationmentioning
confidence: 48%
See 1 more Smart Citation
“…For both types of whiskers the researchers cal- culated a signal-to-noise ratio (SNR), or ratio of the power between 'wanted' signals and background noise. Results showed that while both whisker types responded accurately to vortices in the water tank, as supported by the aforementioned studies of these species, harbor seal whiskers significantly reduced background noise compared to California sea lion whiskers (Miersch et al, 2011). Walruses are the other members of the pinnipeds, but the role of their whiskers is largely unexplored.…”
Section: Somatosensationmentioning
confidence: 48%
“…Miersch et al (2011) isolated single whiskers of both animals and tested the whiskers' response to underwater wakes. For both types of whiskers the researchers cal- culated a signal-to-noise ratio (SNR), or ratio of the power between 'wanted' signals and background noise.…”
Section: Somatosensationmentioning
confidence: 99%
“…The next article on vibrissal touch by Miersch et al [45] switches the focus to the pinnipeds-seals and sea lions-which, if mechanoreceptor density is a good indicator, have the most sensitive vibrissae of all mammals. In addition to using their whiskers to investigate objects directly, several pinniped species have been shown to use their whiskers to detect the hydrodynamic trails left by swimming fish.…”
Section: Contents Of Theme Issuementioning
confidence: 99%
“…Since then, a few other parties have carried out studies on the vibration properties of seal whiskers on both real and model specimens [91,143,95]. The important thing to note is that none of the experiments that provided quantitative results were conducted under conditions that allowed the whisker to vibrate freely in response to the flow.…”
Section: Other Whisker Vibration Studiesmentioning
confidence: 99%
“…In the few studies conducted with interfering cylinders of unequal diameter [115,82,40,41,39], it was found that the upstream cylinder also affects the response of the downstream cylinder, reducing its amplitude relative to the single cylinder case, while the frequency of oscillation of the downstream cylinder was found to be either equal to, or twice the value of the frequency of the upstream cylinder. Only one published study [91] has begun to show the harbor seal whiskers' response under WIV conditions.…”
Section: Motivationmentioning
confidence: 99%